Factors affecting the level of halal knowledge of MSEs in food on the island of Bali - Annisa, Nadya Nur; Ali, Khalifah Muhamad; Mahanani, Yekti; Nursyamsiah, Tita (Halal Studies and Society, 2024)
Bali Island is one of the most popular tourist destinations in the world and with the growing preference for the location, especially among Muslim tourists, the demand for halal food has increased. However, due to the predominantly Hindu population in Bali, the availability of halal-certified food remains limited. This study aims to identify the characteristics and examine the level of halal knowledge among food Micro and Small Enterprise (MSE) actors in Bali. It also aims to analyze the factors influencing the halal knowledge of the actors. In order to achieve the stated objectives, the study adopted descriptive analysis and multiple linear regression as its analytical methods. The obtained results showed that the entire level of halal knowledge among food MSE actors in Bali was satisfactory. Additionally, the results also signified that factors such as education level, access to information, and religious awareness were found to significantly and positively influence the level of halal knowledge possessed by the actors.